2013
DOI: 10.5812/ijhrba.10695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Stress Management Skill Training on the Depression, Anxiety and Stress Levels in Drug Addicts after Drug Withdrawal

Abstract: BackgroundStressful life events may cause initiation of drug use among people. The main purpose of this study was to evaluate the effectiveness of stress management skill training on depression, anxiety and stress levels in drug addicts after withdrawal.ObjectivesThe population included all drug addicts after withdrawal in 2012 in Alborz province.Materials and MethodsThe study was quasi-experimental with pretest-posttest design with a control group. Levels of emotional reactions (depression, anxiety and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Among those factors, stress has been identified to be a predictor of depressive disorders. Research conducted by Habibi, Tourani, Sadeghi, and Abolghasemi () provided empirical support for this. Their findings showed that effective the management of stress had a significant impact on reducing the level of depression in drug users.…”
Section: Introductionmentioning
confidence: 72%
“…Among those factors, stress has been identified to be a predictor of depressive disorders. Research conducted by Habibi, Tourani, Sadeghi, and Abolghasemi () provided empirical support for this. Their findings showed that effective the management of stress had a significant impact on reducing the level of depression in drug users.…”
Section: Introductionmentioning
confidence: 72%
“…However, in this regard, the findings of a study conducted to investigate the effect of LST on the people quitting drug indicated that, this program could reduce the anxiety and depression of addicted people who are trying to quit. [20] Additionally, findings of another study on the effect of LST indicated that, this training not only provided effective techniques to counteract stress and emotions, but also improved the quality of life of individuals. [21] Moreover, findings of a longitudinal study indicated that, LST is effective in improving social skills, selfmanagement, and drug resistance, and reduces the risk of substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments that have been made so far include cognitive behavioural therapies, stress management training, encouragement training and motivational intervention. [1,16,[19][20] Various studies have recently been done on LST. Studies conducted have focused on aspects of drug-abuse treatment programs, such as marital satisfaction, quality of life, and stress reduction, which have shown the effectiveness of LST on these factors.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Chronic use of these drugs can cause a variety of neurological changes in specific areas of the brains, leading to severe damage to the individual. Moreover, withdrawal of drugs of abuse is often associated with side effects, such as depression, increased anxiety, nausea, vomiting and stress [9] [10].…”
Section: Substance Abuse and Behavioral Addictionmentioning
confidence: 99%